INTEGRASI NILAI PENDIDIKAN AGAMA ISLAM DALAM ALGORITMA REKOMENDASI MEDIA SOSIAL: STUDI PERILAKU RELIGIUS GENERASI Z DI DESA POPAYA KABUPATEN POHUWATO - Rahmat Dunggio (Al Arsy: Journal of Education, Management and Islamic Thought, 2026)
This study aims to analyze the influence of social media recommendation algorithms on the religious behavior of Generation Z and to examine the integration of Islamic Religious Education (IRE) values within digital systems in Popaya Village, Pohuwato Regency. This research employs a mixed-methods approach involving 20 students selected purposively based on their social media usage intensity. Data were collected through questionnaires, observations, and documentation, and analyzed using descriptive statistical techniques in the form of percentages. The results indicate that 90% of respondents use social media for more than three hours per day, indicating high exposure to digital content. Around 80% of respondents reported that algorithms influence their content consumption habits, while 70% showed interest in religious content when it appears frequently. Furthermore, there is a positive shift in religious behavior, including increased awareness of worship practices (65%), following Islamic preaching accounts (60%), and improved ethical behavior on social media (55%). These findings demonstrate that recommendation algorithms play a significant role in shaping user behavior. Therefore, integrating Islamic values into social media recommendation systems can serve as an effective strategy to enhance the religious character of Generation Z in the digital era.